CKDNET, a quality improvement project for prevention and reduction of chronic kidney disease in the Northeast Thailand - Ubon Cha'on; Kanok Wongtrangan; Bandit Thinkhamrop; Sajja Tatiyanupanwong; Chulaporn Limwattananon; Cholatip Pongskul; Thanachai Panaput; Chalongchai Chalermwat; Worachart Lert-itthiporn; Amod Sharma; Sirirat Anutrakulchai; CKDNET group (BMC, 2020)
Abstract Background The incidence of chronic kidney disease (CKD) is high in the Northeast Thailand compared to other parts of the country. Therefore, a broad program applying all levels of care is inevitable. This paper describes the results of the first year trial of the Chronic Kidney Disease Prevention in the Northeast Thailand (CKDNET), a quality improvement project collaboratively established to curb CKD. Methods We have covered general population, high risk persons and all stages of CKD patients with expansive strategies such as early screening, effective CKD registry, prevention and CKD comprehensive care models including cost effectiveness analysis. Results The preliminary results from CKD screening in general population of two rural sub-districts show that 26.8% of the screened population has CKD and 28.9% of CKD patients are of unknown etiology. We have established the CKD registry that has enlisted a total of 10.4 million individuals till date, of which 0.13 million are confirmed to have CKD. Pamphlets, posters, brochures and other media of 94 different types in the total number of 478,450 has been distributed for CKD education and awareness at the community level. A CKD guideline that suits for local situation has been formulated to deal the problem effectively and improve care. Moreover, our multidisciplinary intervention and self-management supports were effective in improving glomerular filtration rate (49.57 versus 46.23 ml/min/1.73 m2; p < 0.05), blood pressure (129.6/76.1 versus 135.8/83.6 mmHg) and quality of life of CKD patients included in the program compared to those of the patients under conventional care. The cost effectiveness analysis revealed that lifetime cost for the comprehensive health services under the CKDNET program was 486,898 Baht compared to that of the usual care of 479,386 Baht, resulting in an incremental-cost effectiveness ratio of 18,702 Baht per quality-adjusted life years gained. Conclusion CKDNET, a quality improvement project of the holistic approach is currently applying to the population in the Northeast Thailand which will facilitate curtailing of CKD burden in the region.